Kontekstualisasi, Rekontekstualisasi, dan Dekontekstualisasi Pertunjukan Wayang Kulit sebagai Langkah Pembinaan Penonton Wayang Kulit - Timbul Subagya (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2021)
The presence of the audience in arts performance is generally a hope for the art presenters. It is due to the principle that a work of art that is performed aims to convey messages of values to the community. Therefore, the presence of the audience in performing arts needs to be built. In this paper, several steps are presented relating to the audience building especially for the wayang kulit show. The steps include the concepts of contextualization, recontextualization and decontextualization in wayang kulit performances. Through the audience building, it is hoped that the community will always be present every time the art is performed. it is also hoped that, through the three concepts, public enthusiasm for appreciating wayang kulit show will be maintained.